PENYEBAB TERJADINYA MASALAH PROSTITUSI ONLINE DI KOTA SEMARANG - Ade Putra Andana S; Safik Faozi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
Prostitution is an activity that has taken place during the royal era in Java by using women as objects to fulfill the needs of sexual desire. Prostitution is also considered a social problem considering that this problem is the oldest civilizational phenomenon that is still ongoing today in Indonesian society. Prostitution itself comes from the Latin word prottuere which means openly submitting oneself to adultery. Meanwhile, etymologically it comes from the word prostare which means to sell, peddle. The research method is a way of doing something carefully to achieve a goal by searching, recording, formulating and analyzing to compile a report. In this study using empirical research types, in this case the authors use several methods of research that are appropriate in this research method used to obtain maximum results. The causes of online prostitution in the city of Semarang are caused by several factors, including economic, environmental, internet abuse, and others. The legal policy in dealing with online prostitution crimes refers to Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions which explains that every person who intentionally and without rights distributes or transmits or makes it accessible Electronic Information and Electronic Documents that contain content2 that violates decency as referred to in Article 27 paragraph (1) shall be subject to imprisonment for a maximum of 6 (six) years and a maximum fine of Rp. 1,000,000,000.00 (one billion Rupiah). Prostitution is a form of sexual activity that is usually carried out in tandem with other people to achieve a higher level of intimacy or a unique level of cooperation between the two parties to engage in sexual activity.